Ocular myocysticercosis: an unusual case of ptosis - Agrawal, S; Ranjan, Somesh; Mishra, A (Nepalese Journal of Ophthalmology, 2013)
Background: Cysticercosis is common in endemic countries like India. It can have various clinical manifestations depending on the tissue involved. It refers to a parasitic infestation by Cysticercus cellulosae, the larval form of the pork tapeworm or Taenia solium. Objective: To report an unusual case of ocular cysticercosis involving the levator palpebrae superioris and superior rectus muscle of the right eye. Case description: A young, male adult was diagnosed by Magnetic Resonance Imaging (MRI) scan of the skull and orbit to have right-sided ocular cysticercosis. The patient was treated with oral prednisolone and albendazole, to which he showed a significant improvement. Conclusion: Ocular myocysticercosis can be diagnosed by MRI and be treated medically with steroid and albendazole. Nepal J Ophthalmol 2013; 5(10): 279-281 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8745